Diversity of Culturable Actinomycetes from Deepsea Floor of Makassar Strait, Indonesia - Hatmanti, Ariani; Lisdiyanti, Puspita; Widada, Jaka; Wahyuono, Subagus (Oseanologi dan Limnologi di Indonesia, 2018)
With regard to collaboration research called Widya Nusantara Exploration (EWIN) in May-June 2013 and November 2014, a study on isolation of actinomycetes from sediments of Makassar Strait have been conducted. Actinomycetes is one of microbe which has an excellent track record in producing antimikrob and other active substances. But due to terrestrial actinomycetes has been widely explored, then recently researchers began focusing on wide variety of extreme environments, such as marine environment, to screening aktinomisetes in producing new secondary metabolites. A total of 36 strains of actinomycetes were isolated from 10 samples obtained from deepsea floor in Makassar Strait, Indonesia, Direct Dillution Method were best used to isolate the actinomycetes compare to Sodium Dodecyl Sulfida â Yeast Extract Method (SDS-YE Method) and Rehidration Centrifugation Method (RC Method). NBRC-802 media and Actinomycetes Isolation Agar(AIA)(Himedia)media were used as the isolation media. All the isolates were identified by morphological characteristic and by analysis of 16S rRNA gene sequence. Actinomycetes isolated from deepsea floor of Makassar Strait have been dominated by Micromonospora (58%), Verrucosispora (14%)Streptomyces (8%) and Luteipulveratus (5%), however genus Nocardiopsis, Micrococcus, Gordonia, Kytococcus, and Arthrobacter were not dominant (3%). Station 25 in 1.547 m depth was the most abundant of actinomycetes, 18 strains and dominated by the genus Micromonospora which is isolated using Direct Dillution Method and both NBRC 802 or AIA media.